1995
DOI: 10.1007/bf00019180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of plastid pyruvate kinase from castor and tobacco

Abstract: Clones encoding two different forms of plastid pyruvate kinase (PKp; EC 2.7.1.40) have been isolated from both castor and tobacco seed cDNA libraries. One form, designated PKpA, from castor was described in a previous report, and the tobacco homologue of PKpA has now been isolated. In addition, a second cDNA, designated PKpG, has been identified and sequenced in both species. Western blot analysis, using antibodies raised against protein overexpressed from these clones, indicates that they encode the two predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
6
0
7
Order By: Relevance
“…1). As reported previously (Blakeley et al, 1995;Andre et al, 2007), there are two main classes of plastidial PK isozymes (a and b). Our phylogenetic analysis revealed two subgroups of the a and b classes in angiosperms (designated a1, a2, b1, and b2 according to Andre et al, 2007;Fig.…”
Section: Generation Of Potato Tubers With Decreased Pkc Expression Ansupporting
confidence: 65%
“…1). As reported previously (Blakeley et al, 1995;Andre et al, 2007), there are two main classes of plastidial PK isozymes (a and b). Our phylogenetic analysis revealed two subgroups of the a and b classes in angiosperms (designated a1, a2, b1, and b2 according to Andre et al, 2007;Fig.…”
Section: Generation Of Potato Tubers With Decreased Pkc Expression Ansupporting
confidence: 65%
“…The reconstitution of active PK p s from individually purified inactive subunits in this study and the in vivo co-IP results leave little ambiguity as to the heteromeric structure of the Arabidopsis PK p s. Some studies of recombinant PK p polypeptides from developing R. communis endosperm concluded that the PK p -a and PK p -b homologs are distinct enzymes (Blakeley and Dennis, 1993;Blakeley et al, 1995;Wan et al, 1995), while others have determined that the same proteins are actually subunits of a single heteromeric PK p complex (Plaxton et al, 1990;Plaxton, 1991;Negm et al, 1995). The data presented in this article support the conclusion that PK p is a complex composed of two different subunits.…”
Section: Discussionmentioning
confidence: 76%
“…In the PK family of A. thaliana , three genes encode isoforms with putative plastid targeting sequences that present a strong homology with previously characterized plant PKps (Figure 1a; Blakeley et al. , 1995; Negm et al.…”
Section: Discussionmentioning
confidence: 82%
“…The closest homologues of PKp1 and PKp2 have been shown to encode plastidial isoforms of PKs (Figure 1; Blakeley et al. , 1995; Negm et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation